(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to explore how the public relations offices at Al-Zawiya University deal with the algorithms that govern social media platforms. The study seeks to understand the extent of practitioners’ awareness of how these algorithms work and their impact on the delivery of university content to the target audience (students, faculty members, and the local community). The study employs a descriptive methodology and utilizes a questionnaire distributed to the university’s communications staff.